Tafsir dan Tradisi Pesantren: Karakteristik Tafsir al-Ibris karya Bisri Mustofa - Asif, Muhammad (Lajnah Pentashihan Mushaf Al-Qur'an, 2016)
This study seeks to examine some characteristics in Tafsīr al-Ibrīz which is considered to have close relations with the pesantren (Islamic boarding school) tradition. This article is important to see the relevance of a commentary with the pesantren tradition. This study finds that the Tafsīr al-Ibrīz has some characteristics which are not found in the books of the Qur’anic commentaries written in Indonesian or even in Arabic. This paper concludes that the use of characters of the script known as Pegon and hanging translation, besides directly can be function as the tool of analysis in Arabic grammar it is also considered to be the form of effort to maintain the tradition. In addition to that, there are some other characteristics that became the hallmark of Tafsīr al-Ibrīz interpretation namely the use of speech level as part of the subtlety of the language which is based on one’s piety and not based on one’s position; the rejection of the idea of anthropomorphism (tajsīm); and the view that makes the Qur'an as the answer to all the problems of everyday life. According to the author, some of these characteristics are part of what is called by Dhofier in his dissertation, as pesantren tradition.